Pembuatan Ragum Mini Bagian Rahang Tetap dengan Metode Pengecoran Logam sebagai Cinderamata - Zulhendri Zulhendri; Fadillah Hanum; Mulyadi Mulyadi; Asmed Asmed; Aidil Zamri (Jurnal Teknik Mesin, 2023)
Mini vise is a tool to hold a relatively small object. Mini vise also have another function as a souvenirs. This design purpose is to design the mold of mini vise which is simple and effective. Doing the calculation in the procces of making the fix component of the mini vise and doing analysis the effect of mold slope in the procces of casting. The mold material is mildsteel and the case material is aluminium. There are 3 mold for fix component with different inclination angle which are 1̊, 2̊, 3̊. The best cast result is the mold with 3̊ angle. And can be concluded that bigger angle make the take out procces of the result easier.